Implementasi Layanan Konseling Individu Teknik Cognitive Restructuring untuk Menangani Kasus Bullying: Implementation of Individual Counseling Services Cognitive Restructuring Techniques to Handle Bullying Cases - Nur Diana Arofah; Elisabeth Christiana; Lilik Nursilowati (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
Bullying is a big issue that must be prevented because it has a significant impact and can give rise to a negative mindset towards the perpetrators of bullying. A positive mindset must always be held tightly by every individual, especially the victims of bullying. Bullying cases are a serious problem and often occur in educational institutions. From the bullying cases that occurred, researchers wanted to know the extent of success of cognitive restructuring techniques in handling bullying cases in Vocational High Schools using individual counseling services. The methods used in this research are action research methods in counseling guidance (PTBK), observation and interviews. The results obtained from this research are that individual counseling using cognitive restructuring techniques has been proven to be able to overcome bullying cases at school. This is supported by the results of interviews with guidance and counseling teachers that there are significant changes before and after receiving services. So, it can be concluded that through individual counseling services using cognitive restructuring techniques can overcome bullying cases in Vocational High Schools.